Expanded cinema - Curtis, David; Rees, A.L.; White, Duncan; Ball, Steven (New York, NY : Abrams, 2011)
In this book leading scholars from Europe and North-America trace expanded cinema from its origins in early abstract film to post-war happenings and live events in Europe and the US; the first video and multi-media experiments of the 1960s; the fusion of multi-screen art with sonic art and music from the 1970s onwards, right up to the digital age. It brings new perspectives to bear on the work of established American pioneers such as Carolee Schneemann and Stan Vanderbeek as well as exploring expanded cinema in Western and Central Europe, the influence of video art on new media technologies, and the role of British expanded cinema from the 1970s to the present day. It shows how artists challenged the conventions of spectatorship, the viewing space and the audience, to explore a new participatory and performative cinema beyond the single screen.
boek